(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Student engagement is widely recognized as a key factor influencing academic achievement in English Medium Instruction (EMI) classrooms. As higher education institutions increasingly adopt EMI programs, understanding the factors that contribute to student engagement becomes essential. This article examines the relationship between student engagement and academic success in EMI contexts. Drawing on research in language education and motivation, the paper argues that active participation, motivation, and supportive learning environments contribute significantly to improved academic performance. The study highlights the importance of fostering engagement to enhance both language development and subject knowledge acquisition.